Developing European Resources and Alliances in Asian Studies: Anguish and Advantages - Lambert, Bruce Henry Henry (Acta Orientalia Vilnensia, 2005)
Stockholm School of Entrepreneurship & European Institute of Japanese Studies There is great potential to better develop our network of Japan studies institutes across Europe. This includes mechanisms where we can work together to improve research, and to provide better output and services at lower costs. For example, Japan Portal national projects can facilitiate both inward and outward interactions between each nation and Japan, but also can effectively collaborate together and share certain costs and benefits. This paper discusses problems and bottleneck with marketization of university functions, efforts in the wider academy to rise above competitiveness and political interference struggles, and ways in which Japanese studies are particularly challenged. In short, effective collaboration provides ways to survive and thrive in the newly dynamic European environment; specific suggestions are provided.